ASSESSMENT OF THE IMPACT OF VITAMIN - A CASSAVA MULTIPLICATION PROGRAMME ON FARMERS FOR SUSTAINABLE DEVELOPMENT AND FOOD SECURITY IN NORTH CENTRAL NIGERIA - AKAA, C.W.,; AMONJENU A,; AGBULU,; O.N, (Innovare Journal of Agricultural Sciences, 2019)
The study assessed the impact of vitamin - a cassava multiplication programme on farmers for sustainable development and food security in north central Nigeria. Four research questions were answered and four null hypotheses were tested at 0.05 level of significance. The study made use of survey research design. The population for the study was 120,122 respondents. A sample of 392 made up of 291 farmers and 101 facilitators in north central Nigeria was drawn using multistage sampling technique. A 29 - item questionnaire titled ‘Cassava Multiplication Programme Impact Assessment Questionnaire (CMPIAQ) was used for data collection. The CMPIAQ was validated by three experts, one expert in Agricultural Education, one in crop production and one in Agricultural Extension and Communication, all from the Federal University of Agriculture, Makurdi, Benue State. Cronbach alpha reliability method was used to determine the internal consistency of the instrument. A reliability coefficient of 0.93 was obtained. Mean was used to answer the research questions and t-test statistics was used to test the null hypotheses at 0.05 level of alpha. It was found that 5 objectives of vitamin A cassava multiplication programme were relevant to the rural farmers; vitamin A cassava multiplication programme had 9 significant impacts on rural farmers, 10 challenges were faced by rural farmers in adopting the vitamin A cassava multiplication programme and 5 strategies were suggested for improving the vitamin A cassava multiplication programme in north central Nigeria. It was recommended that the three tiers of Government should collaborate with NGOs, CBOs and private organizations to look into the problems faced by farmers trying to adopt the vitamin A cassava multiplication programme, Strategies to improve the vitamin A cassava multiplication programme should be put into practice by the stakeholders in order to boost cassava production among rural farmers in North Central Nigeria among others.